The Impact of Cognition on Motor Learning and Skill Acquisition Using a Robot Intervention in Infants With Cerebral Palsy - Chandrashekhar, Raghuveer; Wang, Hongwu; Rippetoe, Josiah; James, Shirley A.; Fagg, Andrew H.; Kolobe, Thubi H. A. (Frontiers in Robotics and AI, 2022)
Background: Cerebral Palsy (CP) is a neurodevelopmental disorder that encompasses multiple neurological disorders that appear in infancy or early childhood and persist through the lifespan of the individual. Early interventions for infants with CP utilizing assisted-motion robotic devices have shown promising effects in rehabilitation of the motor function skills. The impact of cognitive function during motor learning and skill acquisition in infants using robotic technologies is unclear. Purpose: To assess the impact of cognitive function of infants with and without CP on their motor learning using the Self-Initiated Prone Progression Crawler (SIPPC) robot. Methods: Statistical analysis was conducted on the data obtained from a randomized control trial in which the movement learning strategies in infants with or at risk for CP was assessed during a 16-week SIPPC robot intervention. Cognitive function was measured by the Bayley scales of Infant and Toddler Development – Third edition (Bayley-III) and the motor function was measured by the Movement Observation Coding Scheme (MOCS). The infants were categorized into three distinct groups based on their cognitive scores at baseline: ‘above average’ (n1 = 11), ‘below average’ (n2 = 10), and ‘average’ (n3 = 26). Tri-weekly averages of the MOCS scores (observations at five time points) were used for the analyses. This study involved computing descriptive statistics, data visualization, repeated measures analysis of variances (ANOVA), and survival analysis. Results: The descriptive statistics and plots were generated for the MOCS and Bayley III scores. The repeated measures ANOVAs revealed that there was a statistically significant effect of time (p < 0.0001) on scores of all subscales of the MOCS. A statistically significant effect of interaction between group and time (p < 0.05) was found in MOCS scores of subscales 1 and 2. Plots were generated for the descriptive statistics and survival analyses. Conclusion: The findings in this study reveal the key movement strategies required to move the SIPPC robot, assessed by the MOCS, vary depending on the infants’ cognition. The SIPPC robot is well-matched to cognitive ability of infants with CP. However, lower cognitive ability was related to delayed improvement in their motor skills.